Prevalence and genotypes of hepatitis G virus among hemodialysis patients in Eastern Anatolia, Turkey - Ozdarendeli, A; Toroman, ZA; Kalkan, A; Kilic, SS; Ozden, M; Doymaz, MZ (Karger, 2005)
Objectives: To study the prevalence and genotype distribution of hepatitis G virus (HGV) in hemodialysis patients in East Anatolia, Turkey. Subjects and Materials: Eighty-nine hemodialysis patients and 30 healthy individuals were analyzed by using reverse-transcriptase nested polymerase chain reaction with primers specific for 5' untranslated region. HGV genotyping was performed by PCR and three randomly selected HGV-positive samples were sequenced. Results: Of the 89 hemodialysis patients, HGV RNA was detected in 9 (10.2%). All of our isolates were assigned to genotype 2. Conclusion: Our results showed that hemodialysis patients carry the risk for HGV infection in East Anatolia, Turkey. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: hepatitis G virus; hemodialysis patients; genotypes; East Anatolia; Turkey